A graded, porous composite of natural biopolymers and octacalcium phosphate guides osteochondral differentiation of stem cells - Amann, Elisabeth (2021)
Lesions involving the osteochondral unit are difficult to treat. Biomimetic scaffolds are previously shown as promising alternative. Such devices often lack multiple functional layers that mimic bone, cartilage, and the interface. In this study, multilayered scaffolds are developed based on the use of natural extracellular matrix (ECM)â like biopolymers. Particular attention is paid to obtain a complex matrix that mimics the native osteochondral transition. Porous, spongeâ like chitosanâ collagenâ octacalcium phosphate (OCP) scaffolds are obtained. Collagen content increases while the amount of OCP particles decreases toward the cartilage layer. The scaffolds are bioactive as a mineral layer is deposited containing hydroxyapatite at the bony side. The scaffolds stimulate proliferation of human adiposeâ derived mesenchymal stem cells, but the degree of proliferation depends on the cell seeding density. The scaffolds give rise to a zoneâ specific gene expression. RUNX2, COL1A1, BGLAP, and SPP1 are upregulated in the bony layer of the scaffold. SOX9 is upregulated concomitant with COL2A1 expression in the cartilage zone. Mineralization in presence of the cells is prominent in the bone area with Ca and P steadily increasing over time. These results are encouraging for the fabrication of biomimetic scaffolds using ECMâ like materials and featuring gradients that mimic native tissues and their interface.